BREAKING BARRIERS: CULTURAL BROKERS AND PARENT PARTNERS IN FRESNO COUNTY’S CHILD WELFARE SYSTEM - Martinez, Emily Elizabeth; Williams, David Michael (International Journal of Allied Research in Sociology and Anthropology, 2023)
Annually, more than 400,000 children become part of the out-of-home placement (OOH) system within the United States foster care network (HHS, 2017). Within this demographic, children of color, particularly African American, Latino/Hispanic, and Native American youth, are conspicuously overrepresented among those placed in out-of-home settings (Assink et al., & Stams, 2018; Bowie, 2003; Crofoot & Harris, 2013; Horton & Watson, 2015; Krase, 2015; Shaw et al., 2008). This disproportionality in the foster care system has prompted researchers nationwide to scrutinize its underlying causes and scrutinize the differing outcomes for children of color in comparison to other groups within the foster care system. The present study embarks on an exploration of an inventive approach to reduce the influx of youth of color into out-of-home care, spotlighting a distinctive initiative in California’s central valley known as Cultural Brokers.